(untitled) (Bangladesh Medical Journal, 2019)
Inguinal hernia surgery is a common operation. It has some negative deviation in its postoperative course. Some immediate and chronic complication can make the doom like situation for both patients and surgeons. Regarding the etiology of these complications; debate still exists. Two main objectives of the study was to determine the frequency of postoperative complications of inguinal hernia surgery as well as their level of severity. The study was conducted among the patients admitted at department of Surgery in Rajbari District Hospital. The study period was 24 months; started from January 2015 to December 2016. The patients were enrolled by purposive sampling. A pre-structured, peer-reviewed data collection sheet was used as a tool to record data regarding socio-demographic clinical, surgical and post operative profile. After taking informed written consent all patients were sent for the pre-anesthetic check up. Lichtenstein tension free mesh hernioplasty was done by consultant surgeon. Injection ceftriaxone single dose i/v was used as prophylactic antibiotic. Here in all cases prolene mesh was used manufactured by Jhonson & Jhonson. Data were compiled, edited, analyzed and plotted into tabular and figure form. Out of 124 patients, 37.09% from 21-30 years age group whereas 29.83% from 31-40 years age group. The mean age was 28.79±7.16 years (age range: 17-69 years). Out of 124 patients 34.67% were day laborer, 23.39% were transport laborer and 16.93% were service holder. Among them 26.61% patients admitted as emergency cases and rest 73.38% was admitted as routine cases. After surgery, 26(20.97%) patients experienced post operative complication. Among them 8(30.76%), 6(23.07%) and 12(46.15%) had early, medium and late complications respectively. Besides, 12(46.15%) were categorized as Clavien-Dindo Grade-I whereas 10(38.46%) were categorized as Grade-II 2(7.69%) patients each were categorized as IIIa and IIIb. Emergency admission (46.15%) was the major risk factor. Higher ASA grade, emergency admission, pre-existing pain, severe depression, pre-existing uncontrolled DM and some drugs as such as clopidogrel and aspirin are the significant preoperative risk factors. Pre-existing uncontrolled DM and drug effects can not be corrected in case of emergency surgery. Bangladesh Med J. 2018 Jan; 47 (1): 22-27